2021
DOI: 10.1520/jte20180677
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction Resistance of Different Size/Shape Sand-Clay Mixtures Using a Pair of Bender Element–Mounted Molds

Abstract: The aim of this study is to assess the influences of both the size and shape of sand grains mixed with a clay on shear modulus (Gmax)– and shear wave velocity (vs)–based liquefaction resistance (cyclic resistance ratio, CRR) using an intensive series of bender element (BE) tests. A low plasticity clay (CL) was added to two specific particle gradations (0.15–0.30 mm, and 1.0–2.0 mm) of clean sands with particular shapes (angular and rounded) at the percentages of 5, 10, 15, 20, 30, and 40, by dry weight. The BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Referring to Fig. 4, it can indicate that the maximum value of the shear strength and shear modulus was achieved at value of 50% fine-grained then a further increment on the finegrained led to decrement of the strength of the soil mixture [6,30]. This phenomena can be explained through the inter-granular void ratio aspect [31,32].…”
Section: Geotechnical Datamentioning
confidence: 97%
“…Referring to Fig. 4, it can indicate that the maximum value of the shear strength and shear modulus was achieved at value of 50% fine-grained then a further increment on the finegrained led to decrement of the strength of the soil mixture [6,30]. This phenomena can be explained through the inter-granular void ratio aspect [31,32].…”
Section: Geotechnical Datamentioning
confidence: 97%
“…15). In light of Lade et al [53], Ni et al [54], Zuo and Baudet [55], Cabalar et al [56], with the increase in WBP to its final limit of 30%, the voids of natural soil are gradually filled up. Based on the explanations given in Cabalar, Karabash [57], Gupta et al [22], and the observations made on the results, it can be concluded that the overall behavior of the samples was governed by the void ratio associated with the WBP particles of the tested samples.…”
Section: Unconfined Compressive Strength Testmentioning
confidence: 99%
“…However, with an increase in the Mg 2+ /Ca 2+ molar ratio, the precipitation of carbonate is inhibited and the strength is reduced. Multiple existing studies [22][23][24][25][26] indicate significant variations in reinforcement effects of sands with different properties. Besides the traditional focus on calcium carbonate precipitation, an important indicator for the low-pH approach is calcium carbonate flocculation lag period, which aims to address clogging issues.…”
Section: Introductionmentioning
confidence: 99%